Body mass index as a determinant of clozapine plasma concentrations: a pharmacokinetic-based hypothesis - Kuzin, Maxim; Haen, Ekkehard; Hiemke, Christoph; Bochon, Benjamin; Bochon, Karolina; Gründer, Gerhard; Paulzen, Michael; Schoretsanitis, Georgios (Journal of psychopharmacology, 2021)
Background:Knowledge regarding the impact of body composition measures on pharmacokinetics of antipsychotics is limited.Aims:Our aim was to investigate the impact of body weight and body mass index on clozapine pharmacokinetics using a therapeutic drug monitoring database.Methods:A large therapeutic drug monitoring dataset of clozapine plasma concentrations considering three patient subgroups was analysed: a control group (CLZ0, 20?30 kg/m2, n=266), a group with high body mass index (CLZhigh, body mass index ?30?kg/m2, n=162) and with low body mass index values (CLZlow, body mass index <20?kg/m2, n=27). Comparisons of plasma and dose-adjusted plasma concentrations (C/D) of clozapine were based on the Spearman?s correlation (rs), Kruskal Wallis and Mann-Whitney-U tests. For percentages we used the Pearson chi-square test (?2). To assess effects of confounders we used bootstrapping analysis of covariates.Results/outcomes:Regarding demographic characteristics, groups differed only for sex percentage with more females than males in CLZlow and CLZhigh compared to CLZ0 (p=0.001 for ?2 test). Plasma and C/D values were positively associated with body mass index (rs=0.108, p=0.022 and rs=0.156, p=0.001 respectively). Intergroup differences were observed for plasma and dose-adjusted concentrations of clozapine (p=0.031 and p=0.029 for Kruskal Wallis respectively): post-hoc pairwise comparisons showed higher plasma concentrations and C/D of clozapine in CLZhigh compared to CLZ0 (p=0.014 and p=0.007 respectively for Mann-Whitney U-test), by mean 21 and 18%, respectively. Differences for C/D values remained after accounting for sex (p=0.02).Conclusions/interpretation:In obese patients, bioavailability, distribution or elimination of clozapine may be altered due to increased clozapine deposits in fat tissue and hepatic enzyme activity changes.
Gesehen am 13.08.2021